ANALISIS KESALAHAN PENGUCAPAN HURUF ṢĀD, SĪN, DAN SYĪN DALAM PEMBELAJARAN TAHSIN - Elviani; Rizky Rival Ramadhan; Abdur Rasyid (CV. Adiba Aisha Amira, 2026)
The accurate pronunciation of Arabic letters is one of the essential aspects of Tahsin learning because it directly influences the correctness of Qur'anic recitation. However, many students still experience difficulties in distinguishing letters with similar articulation points, particularly Ṣād (ص), Sīn (س), and Syīn (ش). This study aims to analyze the common pronunciation errors of these three letters and identify the factors contributing to such mistakes in Tahsin learning. The research employs a qualitative descriptive approach through observation, interviews, and documentation of students' recitation practices. The findings reveal that pronunciation errors are mainly caused by limited understanding of makhaarijul huruf, inadequate practice, and the influence of the learners' native language. In addition, the lack of continuous corrective feedback from instructors contributes to the persistence of these errors. The study concludes that the application of intensive Tahsin methods, regular repetition exercises, and direct teacher guidance can significantly improve students' ability to pronounce Ṣād, Sīn, and Syīn correctly. Therefore, strengthening the teaching of makharijul huruf is essential to enhance the quality and accuracy of Qur'anic recitation.